Beyond Racism : (Lynne Rienner Publishers, 2001)
This study explores issues of race, racism, and strategies to improve the status of people of African descent in Brazil, South Africa and the USA. The authors provide in-depth information about each country, together with analyses of cross-cutting themes and trends.